PENGURUSAN DARI PERSPEKTIF ISLAM - Abdul Ghani Azmi, Ilhaamie (Jurnal Syariah, 2019)
The anicle tries to explain the Islamic point of view on management. Several factors are explained which include the history, sources, definitions, objectives, concepts and their implications, principles and values of Islamic management. The writer, later on, gives two examples of Islamic management. It is found that Islamic management is better than the conventional one as the benefits that can be obtained through its implementation are not only for worldly sake but also for Hereafter.